Capital budgets and their role in the rationalization of investment decisions: an applied study on the branches of commercial banks in the city of El Fasher, the state of North Darfur - Sudan - Sabeel, Adam Ahmed Sulaiman; Abdul Rahman, Badruddin Mohammed Ahmed; Al-Rih, Waddah Al-Shazly Abdel-Rahman (Journal of Economic, Administrative and Legal Sciences, 2017)
This study discussed capital budgets and their role in rationalizing investment decisions in commercial banks' branches in El Fasher town with an objective of highlighting the importance of using capital budgets rationalizing investment decisions in commercial banks' branches in the study area and explaining to what extent the working staff in the above mentioned banks aware that using capital budgets will lead to rationalizing investment decisions as well as possessing enough knowledge could be depended on to prepare and implement capital budgets on scientific bases. The Study depended on primary sources to acquire the related data using comprehensive survey method due to the limited population size which consist of the all working forces in commercial banks' branches in the study area (50) and a questionnaire was used for this purpose. The Study depended also on secondary sources such as books, sand internet to acquire additional data. Statistical methods, namely frequency tables, percentages and Chi-Square were used to manipulate the data and testing the reach hypotheses. The obtained results revealed that investment decisions consider as one of commercial banks' branches managers’ major tasks in the study area, and these branches always identify different investment alternatives then choosing the best one. Additionally, Investment diversification is considered one of fundamental banks policies in order to minimize risk associated with these investments. Chi-Square test analysis revealed that the working forces in these branches aware that the process of investment decisions is considered one of commercial banks' branches managers’ major tasks, and they aware of the importance of using the capital budgets rationalizing investment decisions tasks, additionally, thy possess enough knowledge that could be depended on to prepare and implement capital budgets on scientific bases, all at 0.05 significant level. the study recommends that it is important to support capital budgeting culture, be sure of the soundness of investment alternative chosen; building the banks' working forces capacities in fields of using capital budgets rationalizing investment, and sharing of the staff at different division and departments in the process of investment decisions.
Keywords: capital budgeting; investment decisions; commercial banks; El Fasher